2022
DOI: 10.1111/caim.12523
|View full text |Cite
|
Sign up to set email alerts
|

Managers' brokerage for business model innovation: A case study

Abstract: Business model innovation is recognized as a key process for strengthening firms' performance in situations of strong competitive pressure and environmental changes. This process is driven by intra-organizational advice networks between managers, which exchange different types of advice based on organizational learning mechanisms such as cognitive search (how to conceptualize and create a novel business model) and experiential learning (how to adapt and experiment a novel business model. Investigating what are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 118 publications
0
3
0
Order By: Relevance
“…In this ecosystem, managers' decisions on BMI are influenced by customers, suppliers and partners' needs (Snihur & Tarzijan, 2018). All these actors are concerned by the changes entailed in BMI, and companies must take their insights into account (Demil et al, 2015; Ghinoi & Di Toma, 2022; Snihur & Zott, 2020). Under conditions of high environmental dynamism, insights from these actors evolve quickly (Hock‐Doepgen et al, 2021; Sosna et al, 2010) and, as such, flexibility and openness become crucial (Deligianni et al, 2017; Ricciardi et al, 2016).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…In this ecosystem, managers' decisions on BMI are influenced by customers, suppliers and partners' needs (Snihur & Tarzijan, 2018). All these actors are concerned by the changes entailed in BMI, and companies must take their insights into account (Demil et al, 2015; Ghinoi & Di Toma, 2022; Snihur & Zott, 2020). Under conditions of high environmental dynamism, insights from these actors evolve quickly (Hock‐Doepgen et al, 2021; Sosna et al, 2010) and, as such, flexibility and openness become crucial (Deligianni et al, 2017; Ricciardi et al, 2016).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…Managers can update their knowledge base, making sense of changes and adapting the strategies of their companies (Hock‐Doepgen et al, 2021). In addition, learning‐oriented managers can understand when it is the right moment to shift to a new strategy, anticipating environmental challenges (Ghinoi & Di Toma, 2022; Pearce & Conger, 2003) and managing emerging opportunities (Uotila, 2017). Finally, prior research has also shown that the dynamism of the environment reinforces managers' learning orientation over time, as such increasing the possibility to engage in innovative activities (Mammassis & Kostopoulos, 2019).…”
Section: Theory and Hypotheses Developmentmentioning
confidence: 99%
“…The sudden extreme shock of the recent COVID‐19 crisis has notably caused SMEs to see their usual ways of doing business obstructed in an unprecedented way, which has directly affected and challenged the competitiveness of many firms' business models (Batjargal et al, 2023; Fairlie & Fossen, 2022). Recent studies have therefore suggested that engaging in business model innovation (BMI), which, according to the dominant view in the innovation management literature, involves making fundamental changes to one or more of the key elements of the firm's existing business model, can be for SMEs an important strategic response to address severe crises like COVID‐19 as it can create new competitive advantages for the firm (Breier et al, 2021; Ghinoi & Di Toma, 2022; Ireland, Covin, & Kuratko, 2009; Kraus et al, 2020; Menter, Göcke, Zeeb, & Clauss, 2023). However, BMI is a highly challenging and uncertain strategic undertaking, and empirical knowledge on its emergence, especially during crises, remains sparse as the field is still evolving and mainly studied qualitatively (Andersen, Aagaard, & Magnusson, 2022; Foss & Saebi, 2017; Zhang, Antonialli, Bonnardel, & Bareille, 2023).…”
Section: Introductionmentioning
confidence: 99%